Peningkatan Hasil Belajar Siswa dalam Pembelajaran Pendidikan Kewarganegaraan (PKn) dengan Menggunakan Metode Simulasi di Kelas VI SDN 15 Muaro Takung Kec. Kamang Baru - Tri Eka Pidani (Warta Pendidikan | e-Journal, 2020)
The research begins with the fact that the learning process in SD is monotonous, the development of the cognitive, affective and psychomotor aspects of students is not well developed, so that the student learning outcomes of Civics are not optimal. To overcome this problem, a simulation method is used. The research objective was to describe the increase in student learning outcomes in Civics learning with the simulation method in class VI SDN 15 Muaro Takung Padang. This research is a classroom action research using qualitative and quantitative approaches. Research includes (1) planning, (2) implementation, (3) observation, and (4) reflection. The research was conducted in two cycles, carried out collaboratively with class teachers and peers. Data collection through observation and tests. The research subjects were 18 grade students of SDN 15 Muaro Takung in the second semester of the 2018/2019 academic year. The research, which was conducted using the simulation method, has succeeded in improving the Civics learning outcomes of the VI grade students of SDN 15 Muaro Takung. The results of the RPP assessment obtained the RPP assessment score for the first cycle of meeting 1 = 56.25%, meeting 2 = 62.5%. Cycle II meeting 1 = 78%, meeting 2 = 81.25%. Implementation of the teacher's aspect in the first cycle of meeting 1 = 58%, meeting 2 = 67%. Cycle II meeting 1 ¬ = 79%, meeting 2 = 90%. The results of observations of aspects of students in the first cycle of meeting 1 = 58%, meeting 2 = 69%, cycle II of meeting 1 = 79%, meeting 2 = 87%. While student learning outcomes in the first cycle of meeting 1 = 59.00, in the first cycle of meeting 2 = 65.28 and in the second cycle of meeting 1 to 71.33, in the second cycle of meeting 2 had an increase with the average obtained that is 84, 78. From the results of the research data analysis, it can be concluded that using the simulation method can improve the understanding and learning outcomes of Civics class VI students of SDN 15 Muaro Takung.